2018
DOI: 10.1093/mnrasl/sly073
|View full text |Cite
|
Sign up to set email alerts
|

The distinguishing signature of magnetic Penrose process

Abstract: In this Letter, we wish to point out that the distinguishing feature of Magnetic Penrose process (MPP) is its super high efficiency exceeding 100% (which was established in mid 1980s for discrete particle accretion) of extraction of rotational energy of a rotating black hole electromagnetically for a magnetic field of milli Gauss order. Another similar process, which is also driven by electromagnetic field, is Blandford-Znajek mechanism (BZ), which could be envisaged as high magnetic field limit MPP as it requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 34 publications
(57 reference statements)
2
79
0
Order By: Relevance
“…This idea was originally suggested by Penrose and Floyed in the late seventies [26], concerning energy extraction from a black hole in the presence of a ergoregion. Since then, many investigations have been carried out in many aspects to examine the implications of Penrose process in various astrophysical domains [46][47][48][49][50][51][52][53][54][55][56].…”
Section: Energy Extraction From Kerr-newman-nut Black Holementioning
confidence: 99%
“…This idea was originally suggested by Penrose and Floyed in the late seventies [26], concerning energy extraction from a black hole in the presence of a ergoregion. Since then, many investigations have been carried out in many aspects to examine the implications of Penrose process in various astrophysical domains [46][47][48][49][50][51][52][53][54][55][56].…”
Section: Energy Extraction From Kerr-newman-nut Black Holementioning
confidence: 99%
“…After that the properties of the electromagnetic field structure around rotating black holes have been considered by various authors. The role of the magnetic field through magnetic Penrose process has been studied by [50][51][52][53][54][55][56]. The similar scenarios in alternative/modified theories of gravity have been studied in [28,[57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…True, in moderately high magnetic fild range, the two seem to be similar. Recently, it has been argued [23] that MPP is a general process that works in all magnetic field range while BZ requires the threshold magnetic field, and for that range the former approximates to the latter. That is BZ is contained in MPP in high field range.…”
Section: Discussionmentioning
confidence: 99%
“…In [10], it is shown that, in realistic cases applied to the Galactic center black hole, even a small charge of the black hole can have non-negligible effects on the observed bremsstrahlung emission profile. We would like to emphasize that the black hole charge plays a key role in the black hole energy extraction processes, such as Blandford-Znajek mechanism and magnetic Penrose process [23]. Discharge of induced electric field by oppositely charged accreting matter drives the rotational energy away from the black hole in both of the processes.…”
Section: Black Hole Chargementioning
confidence: 99%